Treatment of rheumatoid arthritis with biologic and targeted synthetic disease-modifying anti-rheumatic drugs in 2022 – real-world data from the Romanian Registry of Rheumatic Diseases - Elena Rezus; Claudiu C. Popescu; Corina Mogosan; Claudiu Avram; Razvan-Constantin Ionitescu; Ioana Felea; Ileana-Cosmina Filipescu; Catalin Codreanu (Romanian Journal of Rheumatology, 2023)
Objective. The study aimed at characterizing the evolution of RA treatment with b/tsDMARDs in Romania, since the end of the SARS-CoV-2 pandemic and the national approval of JAKi. Methods. Data on RA patients was obtained from the Romanian Registry of Rheumatic Diseases database between January 1st, 2022, and December 31st, 2022, encompassing all Romanian RA patients fulfilling the national criteria for b/ tsDMARD initiation. Results. The RRBR database contained 5396 active RA patients: 83.2% female, 59.9 years mean age, 13 years median disease duration, 86.7% RF positive, 81.7% ACPA positive, with a high prevalence of cardiovascular comorbidities, 89.8% receiving at least one csDMARD, most often methotrexate (48.7%), with 6.3% on glucocorticoids, 78.8% on bDMARDs (especially etanercept - 27.6%, adalimumab - 18.1% and tocilizumab - 14.0%) and 21.2% on JAKi (most often on baricitinib - 11.4%), with a 58.2% DAS28-defined remission rate and a 34.3% SDAI-defined remission rate. Conclusion. The Romanian cohort of RA patients on b/tsDMARDs observed the both classical phenotypic characteristics of RA and local cohort characteristics. JAKi prescription has gained a significant increase. Capturing data on real-world patients filtered by stringent criteria for high disease activity and poor prognosis factors, the RRBR database proves to be an extremely useful insight into the evolution of RA pharmacologic treatment.